Wasted in Engineering : Story of India's Youth - Prabhu Swaminathan (Notion Press, 2014)
'Engineering padicha nalla future - If you study engineering, you will have a good future.' This is a claim often repeated to children and teenagers by parents and teachers in many parts of India. But only those who have gone through an engineering college life know that it's not completely true. There is a difference between calling yourself as an engineering graduate and an engineer. India produces millions of engineering graduates like you and me but only very few of us are actual engineers. Many of us just graduate with an engineering degree, with an artistic dream in mind. What do you think is the difference between engineers in many countries around the world and engineers from India? In other countries, if David Pascal studied electrical engineering in college, few years later you can find him working as an electrical engineer. In India, if Ram Krishnamurthy studied electrical engineering, few years later you can find him working in a completely irrelevant field like software coding, banking, photography and even movie directing. This book is not about the few engineering students in your class who love engineering. I don't hate them. In fact, I am very jealous that they study what they love. This book is about the majority of engineering graduates whose lives are wasted in engineering and is intended to tell you why you should make an attempt in pursuing your real passion, instead of being suffocated under the weight of an engineering degree. This is a story of India's Youth. Welcome to India, the land of Wasted Engineers